National support for the European integration project: Does financial integration matter? - Patricia Esteve-González; Helmut Herwartz; Bernd Theilen (Economics & Politics, 2021)
We analyze in how far market perceptions of actual financial integration affect EU integration support at the country level. As indicators of realized states of integration in financial markets we rely upon yield differentials of long-term government debt. To identify particular situations that could undermine the integration process, we suggest a new measure of EU integration risks that fulfills a number of properties which are desirable to ensure its informational value. Our results indicate that tensions to finance public debt in integrated financial markets are the main contributor to weakened support for EU integration. Particularly, large yield spreads increase the polarization on this issue at the country level. Moreover, as a confirmation of a-priori expectations, we find that the national support for EU integration sees a fostering in times of economic upswing and under beneficial structural EU funding. These results indicate that it becomes crucial to monitor increasing international yield differences as they could prepare the ground for claims for EU disintegration policies, thereby, threatening future advances of the EU integration project.
Keywords: 330; EU15; financial market integration; long-term government bond yields; national support for European integration; polarization